Monitoring of Sulfamethoxazole and Sulfadiazine in Chicken Meat in Lahore City, Pakistan - Tipu, M.Y.; Muhammad, K.; Abbas, M.; Khan, A.M.; Ali, S. (Asian Journal of Chemistry, 2011)
Residues of sulfa drugs (sulfamethoxazole and sulfadiazine) were determined in the samples of chicken meat collected from four towns of city Lahore, Pakistan. Total 116 samples were collected during a period of 5 months (June through October 2009) and were processed for monitoring sulfamethoxazole and sulfadiazine through high performance liquid chromatography (HPLC). Each sample was analyzed separately for monitoring each of the sulfa drugs using UV detector of HPLC. Twenty seven percent meat samples (31/116) contained sulfamethoxazole and 10 % (12/116) contained sulfadiazine levels exceeding the tolerance levels for residues of animal drugs (0.1 ppm). The mean value of sulfamethoxazole was 1.11 ranged 0.01-3.91 μg/mL whereas mean value of sulfadiazine was 0.54 ranged 0.01-1.06 μg/mL. Residues of sulfa drugs in the chicken meat samples is an enormous health risk factor for end consumers. There is need to improve regulatory conditions of marketable poultry meat in the city that will mitigate the sulfa drug residues in chicken meat available for general public.